THE ROLE OF ORGANIZATIONAL COMMUNICATIONS IN ENSURING OF THE EFFICIENCY OF ACTIVITY IN THE CONDITIONS OF MODERN BUSINESS - Galіuk I. B. (The actual problems of regional economy development, 2019)
The article defines internal communications, which are intended to enable the employee to understand the corporate culture, goals and values of the organization. The main features of effective internal communications are highlighted in the article: informative content; clarity; timeliness; independence and impartiality; conciseness. At the same time, the qualities of the employees engaged in the formation of internal communications were defined, namely: openness, honesty, ability to dialogue. In this work the channels of internal communication are considered: vertical, horizontal and internal. Particular attention is paid to the internal communications system, which is a complex of information channels that enable the provision of business, intellectual and emotional data within the organization between employees. The main tools of internal communication are considered: information, communication, analytical and organizational. The main aspects of the evaluation of the effectiveness of the internal communications system, namely the number of communication channels; quality of work that requires simultaneous torment of different units; the number of intermediate links in the transmission of information; timely dissemination of information; balance between vertical and horizontal communications within the company, between documented and formal means; the state of social and psychological climate in the team; number of informal communications. The issue of internal communications audit is covered, the effectiveness of which and the attitude to which personnel of all categories depends largely on what actions the managers will take on its results, as well as on the degree of transparency and accessibility of results. This issue needs further study in order to detail the process of building organizational communications.